Remarkable insensitivity of acorn ant morphology to temperature decouples the evolution of physiological tolerance from body size under urban heat islands. (October 2019) - Yilmaz, Aaron R.; Chick, Lacy D.; Perez, Abe; Strickler, Stephanie A.; Vaughn, Selby; Martin, Ryan A.; Diamond, Sarah E.
Abstract: Environmental temperature can alter body size and thermal tolerance, yet the effects of temperature rise on the size-tolerance relationship remain unclear. Terrestrial ectotherms with larger body sizes typically exhibit greater tolerance of high (and low) temperatures. However, while warming tends to increase tolerance of high temperatures through phenotypic plasticity and evolutionary change, warming tends to decrease body size through these mechanisms and thus might indirectly contribute to worse tolerance of high temperatures. These contrasting effects of warming on body size, thermal tolerance, and their relationship are increasingly important in light of global climate change. Here, we used replicated urban heat islands to explore the size-tolerance relationship in response to warming. We performed a common garden experiment with a small acorn-dwelling ant species collected from urban and rural populations across three different cities and reared under five laboratory rearing temperatures from 21 to 29 °C. We found that acorn ant body size was remarkably insensitive to laboratory rearing temperature (ant workers exhibited no phenotypic plasticity in body size across rearing temperature) and among populations experiencing cooler rural versus warmer urban environmental temperatures (no evolved differences in body size between urban and rural populations). Further, this insensitivity of body size to temperature was highly consistent across each of the three cities we examined. Because body size was robust to temperature variation, previously described plastic and evolved shifts in heat (and cold) tolerance in acorn ant responses to urbanization were shown to be independent of shifts in body size. Indeed, genetic (colony-level) correlations between heat and cold tolerance traits and body size revealed no significant association between size and tolerance. Our results show how typical trait correlations, such as between size and thermal tolerance, might be decoupled as populations respond to contemporary environmental change. Highlights: For terrestrial ectotherms, thermal tolerance and size are positively associated. Rising temperatures are predicted to increase heat tolerance but decrease size. Urban heat islands are replicated mesocosms to explore thermal effects on traits. Acorn ants do not exhibit plastic or evolved body size responses to urban warming. Acorn ant urban evolution of heat (and cold) tolerance is independent of body size.